Effect of Biofertilizer Dosage on Formulasion and Biomass of Azolla microphylla on Zooplankton Abudance in Peat Soil Containers - Irsal simbolon; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abtrack This research was conducted from October 1th to December 31st, 2017 in the Kualu Nenas Village, Tambang District, Kampar regency, Riau Province. The purpose of this study was to determine the effect of formulation biofertilizer doses, and Azolla microphylla biomass on zooplankton abundance in each treatment. This research method uses experimental design with factorial experiments with Randomized Block Design (RBD). The first treatment used a formulation (P) biofertilizer dose without formulation biofertilizer dose (P0), 300 g/m2 (P1) formulation biofertilizer dose, formulation 450 g / m2 (P2) biofertilizer dosage, 600 g/m2 (P3) formulation biofertilizer dose, the biofertilizerdosage formulation is 750 g/m2 (P4). And the second treatment is the biomass of Azolla microphylla (B) without the biomass of Azolla microphylla (B0), biomass of Azolla microphylla 20 g/m2 (B1), biomass of Azolla microphylla 40 g/m2 (B2), biomass of Azolla microphylla 60 g/m2 (B3) . The results of this study showed that the biofertilizer dosage formulation had an effect on the abundance of zooplankton. The best treatment for formulation biofertilizer doses was P2 (450 g/m2) with an abundance of zooplankton 496 ind/l. The biomass Azolla microphylla had an effect on the abundance of zooplankton in the best treatment for biomass Azolla microphylla is B1 (20 g/m2) with an abundance of zooplankton 489 ind/l. Then the best of the combination factors used in this study was P2B1 (450 g/m2 and 20 g/m2) with an abundance of zooplankton 10,500 ind/l. Measurements of water quality parameters such as Temperature, pH, DO, CO2, Nitrate, and Orthoposfat, are categorized as good and supportive for cultivation on peatlands. Keyword: Formulation Biofertilizer, Biomass Azolla microphylla, Zooplankton, Peatland